2009
DOI: 10.1002/app.29598
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical solution copolymerization of the ionic liquid monomer 1‐vinyl‐3‐ethylimidazolium bromide with acrylonitrile

Abstract: Ionic liquid monomer 1-vinyl-3-ethylimidazolium bromide (ViEtIM þ Br À ) was first used to copolymerize with acrylonitrile (AN) successfully under various conditions. This was achieved with azobisisobutyronitrile as the initiator and dimethyl sulfoxide as the solvent. The kinetics of this copolymerization were studied. The values of the monomer apparent reactivity ratios were calculated by the Kelen-Tü dos method. The apparent reactivity ratios of ViEtIM þ Br À (r ViEtIMþBrÀ ) and AN (r AN ) were similar at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…It is interesting that PB 1 A 12 shows nearly the same carbonization yield to that of pure PAN, indicating that the small molar ration of IL content can improve the carbonization yield of PB x A y . 37 Here we presume that the imidazolium ring groups may occur a dynamic cyclotrimerization reaction with nitrile groups, 28 which increased the carbonization yield of the copolymers. Similarly, the nitrogen content of the produced carbon materials improved with an increased molar ratio of AN.…”
Section: Carbonization Of Polymersmentioning
confidence: 92%
“…It is interesting that PB 1 A 12 shows nearly the same carbonization yield to that of pure PAN, indicating that the small molar ration of IL content can improve the carbonization yield of PB x A y . 37 Here we presume that the imidazolium ring groups may occur a dynamic cyclotrimerization reaction with nitrile groups, 28 which increased the carbonization yield of the copolymers. Similarly, the nitrogen content of the produced carbon materials improved with an increased molar ratio of AN.…”
Section: Carbonization Of Polymersmentioning
confidence: 92%
“…Polymerized ionic liquids (poly(IL)s) are a relatively new class of charged polymers (typically cationic) that combine the unique thermal, chemical, and transport properties of ionic liquids (ILs) with the physical and mechanical properties of polymeric materials. The result is a macromolecular system implicitly suited for a range of valuable engineering applications, most notably those involving selective transport phenomena in energy and energy industry related technologies. The predominance of the recent synthetic efforts to produce poly(IL)s have focused on repeat units containing charged imidazolium groups, , some of which have already shown considerable promise as membrane materials for CO 2 /light gas separations, , solid-state ion conductors, and electrochemical devices. , Such target applications are predicated on exploiting the inherent CO 2 gas solubility, ion conductivity, and tunable amphiphilicity associated with the charged imidazolium species. However, true performance optimization in these applications requires an ability to tune not only the charge or gas molecule transport behavior but the mechanical properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…This enables ionic liquids to be potential solvents to replace volatile organic solvents in fabricating novel materials [15][16][17][18][19][20][21]. It was reported that ionic liquids can act as efficient plasticizers for many polymers, such as poly (vinyl alcohol) [22] and poly (methyl methacrylate) [23].…”
Section: Introductionmentioning
confidence: 99%